2018
DOI: 10.1111/bjd.16093
|View full text |Cite
|
Sign up to set email alerts
|

Towards global consensus on core outcomes for hidradenitis suppurativa research: an update from the HISTORIC consensus meetings I and II

Abstract: Summary Background A core outcomes set (COS) is an agreed minimum set of outcomes that should be measured and reported in all clinical trials for a specific condition. Hidradenitis suppurativa (HS) has no agreed-upon COS. A central aspect in the COS development process is to identify a set of candidate outcome domains from a long list of items. Our long list had been developed from patient interviews, a systematic review of the literature and a healthcare professional survey, and initial votes had been cast i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
40
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 20 publications
0
40
0
Order By: Relevance
“…79 Participants of the HISTORIC initiative considered that items related to the QoL of HS patients were important to be included in the core outcome set. 10 Recommendations for treatment strategy based on HS severity and HRQoL changes, as is now standard in psoriasis, may be beneficial. This approach was already taken concerning long-term adalimumab efficacy in HS patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…79 Participants of the HISTORIC initiative considered that items related to the QoL of HS patients were important to be included in the core outcome set. 10 Recommendations for treatment strategy based on HS severity and HRQoL changes, as is now standard in psoriasis, may be beneficial. This approach was already taken concerning long-term adalimumab efficacy in HS patients.…”
Section: Discussionmentioning
confidence: 99%
“…A number of items for a core domain outcome set have been proposed by the Hidradenitis Suppurativa Core Outcomes Set International Collaboration (HISTORIC). 10 Clinical signs and the secondary effects on daily and social life of HS patients often cause significant impairment of health-related quality of life (HRQoL). Previous reviews on HS underlined the high impact of disease on patients' lives and the absence of HS-specific HRQoL instruments.…”
Section: Introductionmentioning
confidence: 99%
“…Periodic worsening of HS symptoms is a well-known aspect of HS and is referred to as disease flare by patients and clinicians. [5][6][7]17 The importance of HS flare is underscored by its inclusion among the core set of outcome domains recommended for future HS clinical trials [5][6][7] and its rank as second highest among topics for research among over 1400 topics. 17 However, this review illustrated the use of the term in 27 papers but the paucity of definitions for the term, as only two studies included a definition.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, an international multistakeholder group reached consensus on a core outcome set of domains for HS clinical trials and made recommendations for future outcome assessments. [5][6][7] Concurrently with this, considerable effort has been put into developing patient-reported and clinician-reported measures for HS. [8][9][10][11] The HS core outcome set specifically recommended assessment of HS flare, although it does not recommend specific measures or perspectives, such as reported by the patient or clinician.…”
mentioning
confidence: 99%
“…8 Recently, an international multistakeholder group reached consensus on a core outcome set of domains for HS clinical trials and made recommendations for future assessment of physical signs of HS. [9][10][11] The recommendations specifically suggested that assessment of physical signs of HS include assessment of ulceration, oedema, erythema, anatomical location and body surface area (BSA). 9 In contrast, the vast majority of existing HS assessment instruments rely on specific terminology for lesion morphology, discriminating among lesion morphologies, as well as on counting the number of each type of lesion, which can be problematic.…”
mentioning
confidence: 99%